Analysis of Construction Service Requirements towards Minimum Standards of Work Knowledge of Vocational High School Students - Rolly Robert Oroh (Universitas Ahmad Dahlan, 2023)
Vocational high school graduates in Indonesia still show a low level of employment in the construction services industry sector. The aim of this research is to find a classification of vocational high school students' occupational knowledge attainment levels that construction services require in carrying out concrete construction work. This research uses descriptive research methods. This research data was obtained through surveys, observations and focus group discussions with construction service actors. The research data collected was then categorized based on work indicators, and analyzed for conformity with Indonesian national work competency standards in the concrete structure work category. The results of the study found that the minimum work knowledge standards of vocational high school students who must meet the needs of construction services in carrying out concrete construction work are understanding about the installation of scaffolding, the making of formwork, the assembling of reinforcement, the installation of reinforcement, and the casting of concrete.